The impact of strategic fit between resource orientation and market orientation towards new product development performance: A proposed framework - Mohd Zamani, Siti Norhasmaedayu; Ashari, Hasbullah; Abdul Talib, Asmat Nizam (2010)
Resource orientation (RO) and market orientation (MO) are two important strategic orientations that have significant impact towards new product development (NPD) performance. Although scholar has examined the RO and MO individually, limited research has evaluated and compared their effect on new product success in one study. Furthermore, only a few have matched the fit between both strategies and tests their effect on firm performance and none of them so far has investigated into the role of internal and external environment factors on the relationship between the fit of both strategies towards NPD performance. The purpose of this paper is to develop a conceptual framework of the impact of strategic fit towards NPD performance. The objective of the study is to determine the effect of strategic fit between RO and MO towards new product development performance. Specifically, want to evaluate whether single strategy or the fit between both strategies will have the greater impact on new product development performance. Besides that, the research will investigate the role of internal (i.e., firm innovativeness and competitive strength) and external environmental variables (i.e., market turbulence and technological turbulence) on the relationship between two strategic orientations and performance.This study will provide the firm with clear guidelines about how they may achieve higher performance level in their firms. This would enable firms to benchmark their firm’s strengths and weaknesses especially in implementing the strategic orientation within the firm.